Politeness maxims found in kick Andy Talk Show “Beasiswa Mengubah Nasib” - Tiarma Intan Marpaung; David Togi Hutahaean (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research aims to classify the type of politeness maxims and the contextual meaning of the speakers’ utterances in using politeness maxims found in Kick Andy Talkshow. The data source of this research was YouTube “Kick Andy Talkshow” which was aired on 5th November 2019. The theory of politeness maxims by Grice and the theory of contextual meaning by Windi. The research method was descriptive qualitative research with content analysis. The result showed that there were 39 politeness strategies found in Kick Andy Talk Show, they were: 6 types of politeness maxims. There are 5 data of tact maxims, 5 data of genorsity maxims, 6 data of approbation maxims, 10 data of modesty maxims, 11 data of agreement maxims, and 2 data of sympathy maxims. And there were 36 contextual meaning found in Kick Andy Talk Show, they were contex of situation 7 data, contex of purpose 8 data, contex of place 6 data, contex of time 6 data, and contex of ocject 9 data. It can be concluded that there are many types of politeness maxims and contextual meanings found in the Kick Andy Talkshow.